The natural history of compensated cirrhosis due to hepatitis C virus: A 17‐year cohort study of 214 patients - Sangiovanni, Angelo; Prati, Gian Maria; Fasani, Pierangelo; Ronchi, Guido; Romeo, Raffaella; Manini, Matteo; Del Ninno, Ersilio; Morabito, Alberto; Colombo, Massimo (Hepatology (Baltimore, Md.), 2006)
Large databases of consecutive patients followed for sufficiently long periods are needed to establish the rates, chronology, and hierarchy of complications of cirrhosis as well as the importance of other potential causes of liver disease. In accordance with this goal, a cohort of patients with compensated cirrhosis due to hepatitis C virus (HCV) was followed for 17 years. Two hundred and fourteen HCV RNA–seropositive patients with Child‐Pugh class A cirrhosis who had no previous clinical decompensation were prospectively recruited and followed up with periodic clinical and abdominal ultrasound examinations. During 114 months (range 1–199), hepatocellular carcinoma (HCC) developed in 68 (32%), ascites in 50 (23%), jaundice in 36 (17%), upper gastrointestinal bleeding in 13 (6%), and encephalopathy in 2 (1%), with annual incidence rates of 3.9%, 2.9%, 2.0%, 0.7%, and 0.1%, respectively. Clinical status remained unchanged in 154 (72%) and progressed to Child‐Pugh class B in 45 (21%) and class C in 15 (7%). HCC was the main cause of death (44%) and the first complication to develop in 58 (27%) patients, followed by ascites in 29 (14%), jaundice in 20 (9%), and upper gastrointestinal bleeding in 3 (1%). The annual mortality rate was 4.0% per year and was higher in patients with other potential causes of liver disease than in those without them (5.7% vs. 3.6%; P = .04). In conclusion, hepatitis C–related cirrhosis is a slowly progressive disease that may be accelerated by other potential causes of liver disease. HCC was the first complication to develop and the dominant cause for increased mortality. (HEPATOLOGY 2006;43:1303–1310.)